2019
DOI: 10.1108/ccij-01-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corporate social responsibility activities for refugees

Abstract: Purpose When in the Summer of 2015 unprecedented numbers of refugees traveled through Austria, not only public and governmental authorities were challenged to provide support, but also the business sector. Various companies responded to the challenge by organizing relief actions, among them Austrian Federal Railways (OEBB). The purpose of this paper is to analyze the effects of this initiative on stakeholder perceptions and behavior. Design/methodology/approach The case of OEBB served as the research context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Furthermore, these examinations have not offered a distinction between CSR or CSA. For instance, Einwiller, Ruppel, and Strasser, (2019) found that individuals showed higher levels of PWOM when they had a positive attitude toward Austrian Federal Railways' decision to provide passenger transportation for refugees arriving from Syria, Iraq, and Afghanistan. The issue of providing support for the refugees was controversial due to the challenges from opposing parties regarding the concern of economic burden (Einwiller et al, 2019).…”
Section: Corporations As Issue Advocatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these examinations have not offered a distinction between CSR or CSA. For instance, Einwiller, Ruppel, and Strasser, (2019) found that individuals showed higher levels of PWOM when they had a positive attitude toward Austrian Federal Railways' decision to provide passenger transportation for refugees arriving from Syria, Iraq, and Afghanistan. The issue of providing support for the refugees was controversial due to the challenges from opposing parties regarding the concern of economic burden (Einwiller et al, 2019).…”
Section: Corporations As Issue Advocatesmentioning
confidence: 99%
“…For instance, Einwiller, Ruppel, and Strasser, (2019) found that individuals showed higher levels of PWOM when they had a positive attitude toward Austrian Federal Railways' decision to provide passenger transportation for refugees arriving from Syria, Iraq, and Afghanistan. The issue of providing support for the refugees was controversial due to the challenges from opposing parties regarding the concern of economic burden (Einwiller et al, 2019). However, to our best knowledge, there are no studies that have tested attribution theory in a CSA context to examine the public's WOM intentions in response to a corporation's CSA efforts.…”
Section: Corporations As Issue Advocatesmentioning
confidence: 99%
“…For example, refugee trainees are allowed to attend language courses in working hours. This reflects the changing strategies of companies to become attractive employer and to take social responsibility seriously (Einwiller et al, 2019) also for refugees (Baethge, 2014) by expanding and developing intercultural competencies (Vogel and Scheiermann, 2019).…”
Section: Head Scarfs Childcare and Safety Netstraining Facilities Lan...mentioning
confidence: 99%
“…More research is needed in this vein. Furthermore, we call on researchers to think through the relationship between refugee issues and frameworks for business responsibility—including not only CSR (discussed in one article in this special issue), but also business ethics and human rights (Einwiller et al, 2019; Goethals et al, 2017).…”
Section: A Further Research Agenda For Business Responses To Refugee ...mentioning
confidence: 99%